Peripheral Neuropathy - Armada-Da-Silva, Paulo (IntechOpen, 2014)
Peripheral Neuropathy offers an update on few of the hottest topics of diagnose, treatment and rehabilitation of peripheral nerve injuries. The book is composed of five chapters, each addressing a different topic, ranging from an analysis of the heightened risk of peripheral nerve injury in todays modern societies and what this signifies for the need in taking decisive action to prevent an increase in the numbers of disabled people, to the description of surgical procedures in pediatric patients. The role of regenerative medicine, the development of novel rehabilitative strategies, and the importance of peripheral neuropathy in diabetes are additional topics covered in the book. By reading this book the reader will be offered a general overview of current research and clinical practice in peripheral neuropathys field.